EFL Students’ Experiences on Transactional Speaking Projects - Wardah Wardah; Eni Rosnija (English Department FBS UNP, 2023)
Speaking for Transactional Functions as a course in English foreign language learning curriculum is essentially needed. This Speaking class provides students beneficial activities for the English language speaking skills development and give them a lot of experiences in the process of learning in and beyond the classroom and working through a project. This study aims at describing the students’ experiences on transactional speaking projects. Since this research describes the condition that exists, the most appropriate method used in this research is the descriptive method. Seven EFL students become the participants of the research. An interview are used for the data collection. The result of interview is then transcribed. The responses on the interview show that Students get a lot of benefits from the transactional speaking projects. The projects improve their 21st century skill : communication, collaboration, creativity, and critical thinking. It also improves the skill of technology use and English language skills development. Besides the benefits, the students also face some challenges in doing the project, such as choosing and exchanging the appropriate background for the topic, editing video, and taking turn in conversation. However, the challenges encourage them to learn and do more for the improvement of their knowledge and behaviour. In short, the students get benefial experiences in the projects.